2024
DOI: 10.1039/d3fo03598k
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DSS-induced ulcerative colitis: evaluating the therapeutic potential of WPI–stachyose conjugates

Zi-han Wang,
Guang-yao Zhang,
Cong Sun
et al.

Abstract: The pursuit for food-based alternatives to conventional therapies for ulcerative colitis (UC) demands immediate attention. In prior investigations, we synthesized WPI-stachyose conjugates through the Maillard reaction, identifying them as functional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…He et al demonstrated that oral administration of STA at a dose of 1,500 mg/kg body weight modulates gut microbiota and alleviates DSS-induced acute colitis in mice . Furthermore, Wang et al confirmed that the amelioration of colitis symptoms by STA at a dose of 1,000 mg/kg body weight was closely associated with the restoration of gut microbiota and metabolites . Currently, further investigation is necessary to explore the impact of dosage and purity on the efficacy of STA in UC therapy as well as to find causal evidence between therapy and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al demonstrated that oral administration of STA at a dose of 1,500 mg/kg body weight modulates gut microbiota and alleviates DSS-induced acute colitis in mice . Furthermore, Wang et al confirmed that the amelioration of colitis symptoms by STA at a dose of 1,000 mg/kg body weight was closely associated with the restoration of gut microbiota and metabolites . Currently, further investigation is necessary to explore the impact of dosage and purity on the efficacy of STA in UC therapy as well as to find causal evidence between therapy and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, Wang et al confirmed that the amelioration of colitis symptoms by STA at a dose of 1,000 mg/kg body weight was closely associated with the restoration of gut microbiota and metabolites. 25 Currently, further investigation is necessary to explore the impact of dosage and purity on the efficacy of STA in UC therapy as well as to find causal evidence between therapy and gut microbiota. In this study, three different concentrations of STA (200, 400, and 600 mg/kg body weight) were utilized to demonstrate a dose-dependent alleviation of colitis symptoms (Figure 2).…”
Section: ■ Discussionmentioning
confidence: 99%